Molecular basis for substrate recognition and transport of mammalian taurine transporters - Mingxing Wang; Jin He; Qianwen Cai; Shen-ao Zhang; Ji She (Proceedings of the National Academy of Sciences, 2025)
The taurine transporter (TAUT) mediates cellular taurine uptake, playing a critical role in human health and longevity. In this study, we present cryogenic electron microscopy structures of both mouse and human TAUT in various conformational states. The taurine-bound, occluded forms of mouse and human TAUT reveal the substrate binding pocket and the ion binding sites. The amino group of taurine interacts with Glu406 at the binding site, constituting a key structural feature determining substrate preference. While both imidazole acetic acid and guanidinoethyl sulfonate (GES) inhibit TAUT by competing with taurine for the binding site, GES also functions as a substrate of TAUT. Moreover, mouse TAUT is captured in an inward-open apo conformation, where the tilted movement of transmembrane helix (TM) 1a opens the intracellular gate. Notably, TM6 exhibits two distinct conformational states: the canonical form consisting of two half-helices and a continuous straight helix. In the latter conformation, TM6 partially occupies the substrate binding site, likely promoting taurine release. Together, our findings provide critical insights into the molecular mechanisms by which TAUT recognizes and transports taurine.